Analytical Evaluation Study of Some Characterization of Potable water for an Old Well in Baghdad City - Analytical Evaluation Study of Some Characterization of Potable water for an Old Well in Baghdad Cit (Indian Journal of Forensic Medicine & Toxicology, 2020)
This study involved measuring seventieth tests five of its physically ,temperature, color, turbidity, electricalconductivity and pH and remaining tests were chemical ten of them for heavy metals ,the chlorine and fluorinewere also investigated for water of old well in Baghdad city close to tiger river weekly for six months ,thisstudy showed validity of this well to drink and domestic use within the limit of the properties and elementsstudied only ,through the tests ,all the samples were found to be transparent and non-colored ,there wasnothing left after her leaving ,and the pH ranged from (7.655-7.920) , conductivity (821-908µsemens/cm)and temperature (19.68-23.36ºC) ,the concentrations of elements were (0.031-0.044), (0.038-0,053), (0.009-0.015), (0.019-0.025), (0.004-0.006), (0.009-0.011), (0.029-0.035), (0.108-0.112) ,(0.003-0.005), (95-111),and (0.424-0.571) µg/ml for lead ,cadmium, iron, copper, antimony, cobalt, chromium, zinc, manganese,chlorine and fluorine respectively ,as for nickel, it is not registered, all the tests have been subject to the localand international standards except lead and cadmium, according to international standard only